Homogeneous rhodium(I)-catalysis in de novo heterocycle syntheses - Neuhaus, J; Willis, M (Royal Society of Chemistry, 2016)
Recent research has led to the development of mild, efficient and selective catalytic systems based on Rh(I) complexes. This review summarises the applications of these catalysts to the synthesis of heterocycles from simple building blocks. Included herein are approaches based on cycloisomerisation, cycloaddition, hydroacylation and hydroarylation reactions, as well as various tandem and domino procedures and carbonylation processes.